2018
DOI: 10.1002/2017ja024804
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Saturn's Aurora at Lower Latitudes by Electrostatic Waves

Abstract: In the present paper we have modeled diffuse auroral emissions, which have been observed at lower latitudes as compared to the main auroral arc at Saturn. It is generally accepted that these emissions are generated by precipitation of hot population of magnetospheric electrons on the closed field lines. We have considered the pitch angle diffusion by electrostatic electron cyclotron harmonic waves as the mechanism to diffuse trapped electrons into the atmospheric loss cone. Electrons are thereby precipitated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…These outer boundaries map to a radial distance of 6–7 RnormalS in the magnetic equator plane, corresponding to the inner edge of the region of hot ion/electron plasma as determined in equatorial data (Schippers et al, ; Kellett et al, , ; Carbary et al, ; Carbary, ). The “diffuse” emission observed here and in previous studies is consistent with wave‐driven precipitation from this hot plasma population (Grodent et al, ; Tripathi et al, ), similar to the diffuse outer emission in Jupiter's aurorae (Radioti et al, ).…”
Section: The Outer Emissionsupporting
confidence: 90%
See 1 more Smart Citation
“…These outer boundaries map to a radial distance of 6–7 RnormalS in the magnetic equator plane, corresponding to the inner edge of the region of hot ion/electron plasma as determined in equatorial data (Schippers et al, ; Kellett et al, , ; Carbary et al, ; Carbary, ). The “diffuse” emission observed here and in previous studies is consistent with wave‐driven precipitation from this hot plasma population (Grodent et al, ; Tripathi et al, ), similar to the diffuse outer emission in Jupiter's aurorae (Radioti et al, ).…”
Section: The Outer Emissionsupporting
confidence: 90%
“…Cassini's Ultraviolet Imaging Spectrograph (UVIS) however provided many more observations (visible in, e.g., Radioti et al, ), which will here be exploited to further investigate this signature. It is believed to be caused by hot electrons between 7 and 10 RnormalS (Schippers et al, ) which may reach the ionosphere through pitch angle scattering by plasma waves (Grodent et al, ; Grodent, ; Tripathi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Grodent et al (2010) described these more diffuse outer auroras in the south polar case as a 7-degree-wide emission centered near planetocentric latitude 67°S attributed to suprathermal (~keV) electrons in the middle magnetosphere. Tripathi et al (2018) calculated that the observed diffuse outer emissions could be caused by pitch angle scattering of softer electrons (less than ~250 eV) by electron cyclotron harmonic waves. Lamy et al (2018) observed diffuse outer auroral emissions in HST images at planetocentric latitudes 65-72°N and presented evidence for field-aligned currents at the time when Cassini crossed this secondary oval in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Via cyclotron resonant interactions, ECH waves can pitch angle scatter plasma sheet electrons into loss cone in the terrestrial magnetosphere, leading to the excitation of diffuse auroral emissions (e.g., Ni et al., 2008, 2011a, 2011b, 2012, 2016, 2017; Horne et al., 2003; Lou et al., 2021, 2022; Meredith et al., 2009; Thorne et al., 2010). Electron scattering by ECH waves is also considered as an important mechanism for producing diffuse aurora at Saturn (Tripathi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%